A PASSIONATE GAMERO. OR OF THE AFFILIATE, POLITICAL AND SOCIAL NETWORKS IN COSTA RICA, NICOYA, NICARAGUA, PANAMA AND HONDURAS IN THE 18TH CENTURY, BY JOSÉ TOMÁS ADALID GAMERO Y MUÑOZ - Rivera Hernández, Gina (2021)
The finding of three heartbreak letters in the National Archive of Costa Rica has generated the content of this article. José Tomás Adalid Gamero y Muñoz, was born in Rivas, Nicaragua in 1771, and spends part of his life between Honduras and Nicoya, specifically in the town of Guanacaste. His various jobs, ship captain, landowner, military man and merchant make him generate contacts in Panama, Costa Rica and Honduras; It is in this last colonial province where he marries and loses his life in a tragic way. The letters relate details of the friendship, affiliation, political and economic networks that lead to drawing new facets of the masculinity of the colony, as well as to know in a more intimate way the lives of the people mentioned in the documents. A passionate Gamero, he recounts the sorrows of the loss of a love in the colony, but also introduces the subject of colonial socioaffective networks. This document is intended to be an introduction that leads other researchers to delve into elements of friendly relations, economics, and politics among the inhabitants of colonial Central America. The result is the product of an exhaustive search that exhausted the available sources